2019
DOI: 10.1634/theoncologist.2018-0675
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized Clinical Trials Comparing Active Treatment with Placebo in Metastatic Neuroendocrine Tumors

Abstract: Background. Most guidelines still recommend active surveillance for patients with asymptomatic, unresectable neuroendocrine tumors (NETs). However, recent findings from several randomized placebo-controlled trials suggest that most patients would benefit from active treatment. We conducted a metaanalysis of pooled outcomes from clinical trials in which an active treatment arm was compared with placebo to determine whether active treatment provides a survival advantage. Materials and Methods. This meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…This challenges the exceptional status of metastasizing NET as the only indication for LT in secondary hepatic malignancy. If the outcome of LT for metastasizing NET for the majority of potential recipients is closer to the results reported herein than to the results from one of the few specialized high-volume centers, the option to remain on a palliative chemotherapy course could be a viable alternative for some patients, as it offers comparable long-term patient survival (60-month patient survival after LT in CTS: 55.7 vs. 45.9% and median patient survival of up to 84.7 months with palliative treatment) ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 59%
“…This challenges the exceptional status of metastasizing NET as the only indication for LT in secondary hepatic malignancy. If the outcome of LT for metastasizing NET for the majority of potential recipients is closer to the results reported herein than to the results from one of the few specialized high-volume centers, the option to remain on a palliative chemotherapy course could be a viable alternative for some patients, as it offers comparable long-term patient survival (60-month patient survival after LT in CTS: 55.7 vs. 45.9% and median patient survival of up to 84.7 months with palliative treatment) ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 59%
“…As above mentioned, treatment with [ 177 Lu]Lu-DOTA-TATE is placed as a secondline therapy along with everolimus in midgut NET tumors and as third or fourth line in pancreatic tumors. Despite the lack of data from specific phase III clinical trials, there is positive evidence of efficacy and safety in advanced pancreatic NET patients in which PRRT could surpass on treatment sequencing other targeted therapies [61,62]. Moreover, a potential increasing toxicity used after prior chemotherapy or targeted therapy has been described, which might justify an earlier use of PRRT in selected patients [36].…”
Section: Which Is the Role Of Prrt-lu In Pediatric Population?mentioning
confidence: 99%
“…Recent meta-analyses/reviews including previous randomized control trials [ 61 , 102 , 103 ] of treatments of patients with advanced panNENs/carcinoids, as well as a nationwide population study in the Netherlands [ 104 ], suggest a higher survival benefit with PRRT treatment than the other systemic therapies in these patients. A second recent meta-analysis [ 105 ] compared active surveillance, which is recommended for patients initially diagnosed with metastatic NENs in several guidelines, to active antitumor treatment (somatostatin analogues, sunitinib, everolimus, PRRT), and found that active treatment extended to both PFS and OS. Another recent meta-analysis comparing the cytoreductive effect between different therapeutic agents reports chemotherapy alone (capecitabine/temozolomide) or in combination showed the strongest effect of cytoreduction in patients with advanced panNENs, followed by PRRT and sunitinib [ 106 ].…”
Section: Introductionmentioning
confidence: 99%